Rise and Fall of an Egyptian Oasis: Artesian Flow, Irrigation Soils, and Historical Agricultural Development in El‐Deir, Kharga Depression, Western Desert of Egypt. Issue 6 (14th June 2016) - Bravard, Jean‐Paul; Mostafa, Ashraf; Garcier, Romain; Tallet, Gaëlle; Ballet, Pascale; Chevalier, Yael; Tronchère, Hervé
Abstract : The present study examines the geoarchaeological history of an oasis in Kharga Depression in central Egypt. El‐Deir is renowned for its Ptolemaic temple and Roman fortress on the road from former Hibis (Kharga) to the Nile Valley. During the survey, spring mounds and irrigation soils belonging to an ancient agricultural zone were discovered, and further documented by ceramics found on the site. Our methodology combines the geomorphological interpretation of landforms (especially yardangs) with ceramics and 14 C‐dated charcoal to distinguish and date former agricultural areas in El‐Deir. The results show that the oasis experienced several phases of soil accretion and destruction through time. Playa sediments were deposited in the humid early Holocene and severely eroded by deflation before the onset of irrigated agriculture between Pharaonic and Persian times. Very fast vertical soil accretion occurred in the Ptolemaic period, but irrigation soils were later destroyed during the Roman period by a combination of wind deflation and flash floods (second to fourth century A.D.), suggesting a period of climate instability. The case of El‐Deir invites reevaluation of constructive agencies for the development of irrigated land and destructive agencies as limiting factors for the sustainability of agricultural practices in late antiquity.